PENERAPAN KEBIJAKAN POLA KOMUNIKASI PADA JARING ASPIRASI MASYARAKAT YANG DILAKSANAKAN DI DPRD KOTA PASURUAN PROVINSI JAWA TIMUR - Soentoro Soentoro (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2017)
This process the researchers tried to describe the symptoms as the symptoms manifest themselves on observation in the meaning to collect data that is raised through the experience of the subject.From this research, it can conclude: Basic policy implementation public aspirations network which still not exist in particular, and refer to Peraturan Walikota Pasuruan No. 16 Tahun 2013, (1) Lack of development plan socialization at the village and sub-district cause of less people participation in development plan process or musrenbang (musyawarah rencana pembangunan). Musrenbang results as a form of public aspirations network is not optimal yet, because of the unavailability of human resources personnel who have competence in planning activities at the village and sub-district. (2) Public participation of Pasuruan relation to the budget process, in the case process of participations are considered false: Legislative has not been able to encourage public participation in the budget process of Pasuruan, both in terms of participation and policies of regional planning and budgeting process. People of Pasuruan independently has not been able to formulate problems and draw up a program of proposed activities to resolve these issues, so that people do not have a sense of belonging to the planning of the development. (3) The effectiveness and efficiency of policy implementation public aspirations network by the institution of Pasuruan Parliament if it focuses on participatory planning based on the problems and needs of the community can be obtained through the investigation of problems and needs.